THE EFFECT OF DIGITAL TRAINING AND DEVELOPMENT ON MSME PERFORMANCE, COMPETITIVENESS, AND PRODUCTIVITY WITH COMPETENCE AS AN INTERVENING VARIABLE (A CASE STUDY OF MSMEs IN MOJOKERTO) - Early Harison Mahardhika; Arief Noviarakhman Zagladi (CV. Radja Publika, 2026)
This study aims to analyze the effect of digital training and development on the performance, competitiveness, and productivity of Micro, Small, and Medium Enterprises (MSMEs) in Mojokerto, with competence as an intervening variable. A quantitative approach was employed using a survey method, with data collected through structured questionnaires distributed to MSME actors. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that digital training and development have a positive and significant effect on MSME performance, competitiveness, productivity, and competence. Furthermore, competence also has a significant effect on performance, competitiveness, and productivity, and acts as a mediating variable that strengthens the relationship between digital training and MSME outcomes. The findings highlight the importance of digital-based training in enhancing human resource competence, which ultimately contributes to improved business performance and sustainable competitive advantage. This study provides both theoretical contributions and practical implications for policymakers and MSME practitioners in designing effective digital training programs.